Research of Flyover as a Solution to Congestion of Intersection Junction A Case Study: Jalan Jatingaleh Semarang - Rahmat Mudiono (International Conference on Coastal and Delta Areas, 2015)
Jatingaleh is located in the southern city of Semarang which is a central meeting point between the upper and lower Semarang where the vehicle flows in through a combination of local current and regional traffic, and the flow of vehicles coming in and out from the highway. The main cause of the problems that occurred in the area of Jatingaleh is due to the number of vehicular movement that occurs at the intersections. In view of the above, it is necessary to analyse the existingconditions and proffers some solutions. Before carrying out an analysis, a field surveys at peak hours, for example, in the morning (06:00 to 08:00 am) and afternoon (04:00 to 06:00 pm)should be conducted. The number of vehicles was counted manually with â€œshort-breakcountingâ€ according to types of vehicles. From the analysis study, the author found out that the degree of saturation (DS) was1.61 between Teuku Umar and Setia Budi road during the morning peak hours and 1.56 during the afternoon peak hours. This means that the capacity of the existing road is no longer able to accommodate the traffic flow. One of the solutions for the congestion that occurs at the intersection of Jatingaleh is to apply the efficiency of the intersection that is not in a plot with a Fly over, Underpass and the combination of Fly Over-Underpass. Based on the flow reduction calculation with 3 comparative modeling it show that the Fly Over is the most technically efficient to be applied in this research.